Padronização no processo de compra: o enfermeiro como executor - Oliveira, Marcela Macedo de; Pandolfi, Edgar de Souza; Chiarato, Thays Dutra (Revista Científica da Faculdade de Educação e Meio Ambiente, 2017)
O presente estudo aborda através de uma revisão de literatura, de caráter descritivo, a importância do método de padronização no processo de compra, considerando as perceptíveis dificuldades encontradas neste setor, como falta de embasamento técnico quanto aos modelos de compra utilizados, na aquisição de artigos médico-hospitalares, culminando em desperdícios por baixa qualidade, ou ainda por utilização equivocada aliada à falta de treinamento, devido trocas constantes de materiais. Nesse contexto, acrescenta-se o papel do enfermeiro como executor, ressaltando a importância do mesmo na unidade hospitalar. Desta forma, este estudo apresenta ferramentas para contribuir dentro desse cenário, agregando conhecimento teórico, científico e legal, que possa ser utilizado durante o desenvolvimento da atividade em instituições de saúde, visando racionalizar os gastos e aperfeiçoar os recursos e serviços. A realização deste estudo permite compreender a importância da padronização no processo de compra e seus benefícios juntamente com a participação do enfermeiro na aquisição dos materiais para a inserção de qualidade no âmbito hospitalar. ABSTRACT: The present study addresses, through a literature review of a descriptive character, the importance of the standardization method in the purchase process of nursing materials and equipment, considering the perceived difficulties in this sector, such as the lack of technical purchase for medical and hospital articles, causing waste due to poor quality, misuse due to constant change of models and lack of training to handle them. In this context, it is verified the fundamental role of the nurse as an executor in emphasizing its importance in the hospital unit with tools and theoretical, scientific and legal knowledge for the development of its activities in health institutions, with the objective of rationalizing the expenditures and resources and improve services. Therefore, this study aims to highlight the importance of nurses' standardization and performance in the purchasing process, focusing on the insertion of quality in the hospital context. With the survey carried out, it can be concluded that the participation of the nursing professional in the standardization of the purchasing process, makes the management of medical and hospital resources more efficient by identifying the quantity and quality of materials needed for health professionals to perform their Risk-free activities for you and your patients. As a suggestion for future research, new research on the subject is indicated for the mapping of critical factors of quality success in medical-hospital procedures based on the use of materials and equipment to support the nursing service.